Implementation of Entrepreneurship Education in Family Business Sustainability: A Narrative Study of Mojosari Klepon Traders - Alifah, Luthfi Nur; Rahmawati; Sudarmiatin; Firmansyah, Rizky (PT Maju Malaqbi Makkarana, 2025)
The family entrepreneurship education model is important to emphasize because it is a basic measure of the success or failure of the business sustainability process. The individual process acts as a recipient of education from his family, acting as a motivator, teacher, and at the same time a parent as it should be. All stages of the process are expected to create individual output that has the ability, knowledge, and competence to be an entrepreneur in order to prepare for the sustainability of the family business. This study aims to understand the effectiveness of the entrepreneurship education model and its implementation in the sustainability of the Mojosari klepon trader family business. The approach used is descriptive qualitative which includes data reduction, data presentation and conclusions. The results of the study indicate that parental involvement in providing entrepreneurship education to children has been carried out by providing motivation, support and encouragement in verbal form and involving children in the family business so that children understand business management, so that they understand the basics of how to manage a business when they will continue the leadership of the family business or establish an independent business.